Penerapan Model Kooperatif Tipe Team Games Tournament untuk Meningkatkan Motivasi Belajar dan Sikap Sosial Siswa di SMAN 2 Banjar - Niyah, Dina Rifqo; Sriartha, I Putu Ananda; Citra, I Putu Ananda (Universitas Pendidikan Ganesha, 2024)
This research aims to analyze the significant influence of the application of the team games tournament (TGT) type cooperative model on increasing students' learning motivation and social attitudes, analyze the significant influence of the TGT type cooperative model on students' learning motivation, and analyze the significant influence of the TGT type cooperative model on students' social attitudes. This research design uses a Quasi Experiment with Non-Equivalent Control Group Design. The experimental and control classes were determined using simple random sampling, and an equality test was carried out. Data collection was carried out using questionnaires and documentation sheets. Then, the data was analyzed using the multivariate analysis test (Manova). The research showed that the Cooperative Team Game Tournament model increased students' learning motivation and social attitudes